2015
DOI: 10.1038/labinvest.2015.109
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 activates alveolar epithelial sodium channel gamma via the microRNA-21/PTEN/AKT pathway in lipopolysaccharide-induced inflammatory lung injury

Abstract: Lipoxin A 4 (LXA 4 ), as an endogenously produced lipid mediator, promotes the resolution of inflammation. Previously, we demonstrated that LXA 4 stimulated alveolar fluid clearance through alveolar epithelial sodium channel gamma (ENaC-γ). In this study, we sought to investigate the mechanisms of LXA 4 in modulation of ENaC-γ in lipopolysaccharide (LPS)-induced inflammatory lung injury. miR-21 was upregulated during an LPS challenge and downregulated by LXA 4 administration in vivo and in vitro. Serum miR-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 60 publications
0
48
1
Order By: Relevance
“…These up-regulations were both dose-and time-dependent. These effects were blocked by the inhibitor of AhR and Rp-cAMP, an The expressions of the mRNAs and proteins of the α, β and γ subunits of ENAC were decreased by 1μg/mL LPS, but these decreases were dosedependently reversed by LXA 4, with maximal effect at 10 -7 M. These findings are in disagreement with recent reports which suggest that LXA 4 enhanced the expression of ENaC in A549 alveolar cells [10]. Interestingly, it was found that 10 -6 M LXA 4 was less effective than 10 -7 M. This implies that the effect of LXA 4 was not concentration-dependent.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…These up-regulations were both dose-and time-dependent. These effects were blocked by the inhibitor of AhR and Rp-cAMP, an The expressions of the mRNAs and proteins of the α, β and γ subunits of ENAC were decreased by 1μg/mL LPS, but these decreases were dosedependently reversed by LXA 4, with maximal effect at 10 -7 M. These findings are in disagreement with recent reports which suggest that LXA 4 enhanced the expression of ENaC in A549 alveolar cells [10]. Interestingly, it was found that 10 -6 M LXA 4 was less effective than 10 -7 M. This implies that the effect of LXA 4 was not concentration-dependent.…”
Section: Discussioncontrasting
confidence: 85%
“…ALI/ARDS is a common, devastating clinical syndrome that affects large numbers of patients and has up to 40 % mortality [10]. The current treatment for ALI/ARDS is aimed at removal of polymorphonuclear neutrophils, and alveolar fluid re-absorption.…”
Section: Discussionmentioning
confidence: 99%
“…miRs also play a significant role in kidney maintenance and normal kidney physiology (Sequeira‐Lopez et al, ; Mladinov et al, ). Recent evidence suggests that miRs may be important intermediaries in the hormonal signaling cascades that alter ion transport in both the airway (Qi et al, ; Qin et al, ) and the kidney (Elvira‐Matelot et al, ; Sober et al, ; Robertson et al, ; Edinger et al, ; Butterworth, ; Jacobs et al, ).…”
mentioning
confidence: 99%
“…Lipoxins have been shown to promote the activity and/or expression of many different types of ion channels including epithelial Na + channels, cystic fibrosis transmembrane conductance regulators, ATP-sensitive K + channels, Ca 2+ -activated anion channels, pannexin 1 hemichannels, and canonical subtype of TRP channels (TRPCs). These effects lead to beneficial outcomes with respect to fluid secretion in the airway (Pang et al, 2011; Verriere et al, 2012; Buchanan et al, 2013; Wang et al, 2013; Yang et al, 2013; Al-Alawi et al, 2014; Higgins et al, 2014, 2015; Qi et al, 2015). Recent studies showing similarly beneficial effects from treatment of other n−3 type pro-resolvents have also emerged in the airway field (Hiram et al, 2014; Wang et al, 2014; Colby et al, 2016).…”
Section: Fatty Acid-derived Pro-resolventsmentioning
confidence: 99%